SOX9 regulates expression of the male fertility gene Ets variant factor 5 (ETV5) during mammalian sex development. (October 2016) - Alankarage, Dimuthu; Lavery, Rowena; Svingen, Terje; Kelly, Sabine; Ludbrook, Louisa; Bagheri-Fam, Stefan; Koopman, Peter; Harley, Vincent
Abstract: In humans, dysregulation of the sex determining gene SRY-box 9 ( SOX9 ) leads to disorders of sex development (DSD). In mice, knock-out of Sox9 prior to sex determination leads to XY sex reversal, while Sox9 inactivation after sex determination leads to spermatogenesis defects. SOX9 specifies the differentiation and function of Sertoli cells from somatic cell precursors, which then orchestrate the development and maintenance of other testicular cell types, largely through unknown mechanisms. Here, we describe a novel testicular target gene of SOX9, Ets variant factor 5 ( ETV5 ), a transcription factor responsible for maintaining the spermatogonial stem cell niche. Etv5 was highly expressed in wild-type XY but not XX mouse fetal gonads, with ETV5 protein localized in the Sertoli cells, interstitial cells and germ cells of the testis. In XY Sox9 knock-out gonads, Etv5 expression was strongly down-regulated. Similarly, knock-down of SOX9 in the human Sertoli-like cell line NT2/D1 caused a decrease in ETV5 gene expression. Transcriptomic analysis of NT2/D1 cells over-expressing SOX9 showed that ETV5 expression was increased in response to SOX9. Moreover, chromatin immunoprecipitation of these cells, as well as of embryonic mouse gonads, showed direct binding of SOX9 to ETV5 regulatory regions. We demonstrate that SOX9 was able to activate ETV5 expression via a conserved SOX site in the 5′ regulatory region, mutation of which led to loss of activation. In conclusion, we present a novel target gene of SOX9 in the testis, and suggest that SOX9 regulation of ETV5 contributes to the control of male fertility.